Shariah Disclosure Practices in Malaysian Islamic Banks using the Shariah Disclosure Index - Amin, Nur Afiqah Md; Mohd Ariffin, Noraini; Fatima, A.H. (Universitas Muhammadiyah Yogyakarta, 2021)
Islamic banks are required to ensure their operations and activities comply with the Shariah principles. According to Islamic Financial Services Act (2013) in Malaysia, all operations and activities of Islamic financial institutions including Islamic banks have to comply with decisions made by the Shariah Advisory Council (SAC) of Bank Negara Malaysia (BNM) and the Shariah Committee (SC) of the Islamic financial institution to ensure Shariah compliance. In practice, Shariah compliance is considered a crucial factor by bank stakeholders, especially Muslim customers in their decision to use Islamic financial products. Thus, one of the ways for Islamic banks to convey their Shariah-compliance to their stakeholders is through annual reports. This study examines the level of compliance on Shariah disclosure in the annual reports of Malaysian Islamic banks. A Shariah disclosure index, comprising mandatory and voluntary items, was developed from Bank Negara Malaysia (BNM) guidelines and Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) standards. Shariah disclosure data were collected from the annual reports for the year 2016 of the 16 Islamic banks in Malaysia. Based on Institutional Theory, this study hypothesised high compliance, however the results revealed that none of the banks had full compliance to the mandatory items. Nevertheless, some of these banks disclosed voluntary items. The findings provide useful insights to the regulators and stakeholders on Islamic banks’ compliance on Shariah disclosure. The study also reveals the importance of disclosing additional items in the annual reports of Islamic banks.